Gender and the return migration process: Gulf returnees in Ghana - Md Mizanur Rahman; Mohammed Salisu (Comparative Migration Studies, 2023)
Abstract Labour migration in the context of South-South migration is generally conceived as a multidimensional process that comprises three distinct subprocesses: emigration, immigration, and return migration. There is growing consensus that return migration is the least understood of these three subprocesses. In a similar vein, a gendered analysis has become more integral to migration scholarship today; yet one area where gender matters but has not been thoroughly studied is the return migration process. This paper explores how gender shapes the return migration experiences by reflecting on four transnational sites of return migration such as migrants’ socio-demographic features, working and living conditions in the Gulf, remittance control and use, and finally return and reintegration. Empirically, this research draws on the experiences of selected Gulf male and female return migrants in Accra, Ghana. The study reports that the gender dimension of returnees’ experiences constitutes an avenue of migration research that has the potential to produce a more nuanced understanding of gendered migration scholarship in the Global South.